When bigger is better: the role of polyploidy in organogenesis. Issue 6 (June 2015) - Orr-Weaver, Terry L.
Highlights The large cells that are necessary in plant and animal organs usually are generated by increased ploidy. A large cell has multiple advantages versus a comparable mass of diploid cells. Cell hypertrophy via increased ploidy can produce an envelope or control organ shape. Polyploidy is linked to cell differentiation and function.